ACTN3 genotype influences exercise-induced muscle damage during a marathon competition - Del Coso, J.; Valero, M.; Salinero, J. J.; Lara, B.; Díaz, G.; Gallo-Salazar, C.; Ruiz-Vicente, D.; Areces, F.; Puente, C.; Carril, J. C.; Cacabelos, R. (European Journal of Applied Physiology, 2017)
Purpose: Exercise-induced muscle damage has been identified as one of the main causes of the progressive decrease in running and muscular performance in marathoners. The aim of this investigation was to determine the influence of the ACTN3 genotype on exercise-induced muscle damage produced during a marathon. Methods: Seventy-one experienced runners competed in a marathon race. Before and after the race, a sample of venous blood was obtained and maximal voluntary leg muscle power was measured during a countermovement jump. In the blood samples, the ACTN3 genotype (R577X) and the changes in serum creatine kinase and myoglobin concentrations were measured. Data from RX heterozygotes and XX mutant homozygotes were grouped as X allele carriers and compared to RR homozygotes. Results: At the end of the race, X allele carriers presented higher serum myoglobin (774 ± 852 vs 487 ± 367 U/L; P = 0.02) and creatine kinase concentrations (508 ± 346 vs 359 ± 170 ng/mL; P = 0.04) than RR homozygotes. Pre-to-post-race maximal voluntary leg muscle power reduction was more pronounced in X allele carriers than RR homozygotes (-34.4 ± 16.1 vs -27.3 ± 15.4%; P = 0.05). X allele carriers self-reported higher levels of lower limb muscle pain (7 ± 2 vs 6 ± 2 cm; P = 0.02) than RR homozygotes at the end of the race. Conclusions: In comparison to RR homozygotes, X allele carriers for the R577X polymorphism of the ACTN3 gene presented higher values for typical markers of exercise-induced muscle damage during a competitive marathon. Thus, the absence of a functional a-actinin-3 produced by.